Модель мережі радіодоступу з використанням методу адаптивного формування структури - Гуськов, П. О.; Цуркан, А. С.; Шпур, О. М.; Бугиль, Б. А.; Климаш, М. М. (Видавництво Львівської політехніки, 2016)
Запропоновано метод адаптивного структурного синтезу мережі радіодоступу. Цей метод призначений для побудови мережі радіодоступу з використанням принципів детермінованої та стохастичної геометрії. Використовуючи засоби імітаційного моделювання, розроблено модель гетерогенної мережі, яка залежно від просторової локалізації та розподілу абонентського навантаження формує структуру мережі радіодоступу. Отримано залежності пропускної здатності, системної спектральної ефективності та розподілу навантаження по кожному структурному елементу мережі. Constantly increasing demand by mobile devices for higher data rates and new multimedia services support creates unprecedented challenges for future fifth generation (5G) mobile networks: 1000 times higher system capacity, up to 100 times higher peak user data rates and 10 times lower energy efficiency of today’s 4G networks. This stipulates changes of modern radio access networks (RAN). Existing deterministic approaches for RAN deployment and analysis that are used for optimal resource allocation are not compatible with future multitier heterogeneous networks, especially because of the fixed cells’ radius restrictions and the impossibility to respond to non-uniform load conditions. According to mentioned requirements, reasonable deployment expenditures and consistent quality of experience assurance small cells occur the most reasonable solution. In comparison to macrocells, low-cost small cells offer a significant capacity gain due to spatial reuse of spectrum. This paper presents the new approach for small cells deployment based on adaptive RAN structure synthesis method that generates the base stations on/off switching patterns and serves users by appropriate RAN entities according to current load distribution and network conditions. We consider three-tier Heterogeneous network where we integrate macro-, femtoand picocells. A method for services differentiation between RAN structural entities on different layers that support traffic aggregation is proposed. We developed simulation model that reflects the functioning of a RAN in real time and displays dependences of the network capacity, system spectral efficiency and load distribution on each RAN structural entity. The main advantages of proposed approach are flexibility, adaptability to non-uniform spatially distributed traffic and energy efficiency. The results show that with a slight decrease in the average throughput per UE (2–4 %) was observed the gain in energy consumption, by reducing the number of active elements in RAN structure by 30–40%. Future activities to this work involve assessing the network structure on the number of handovers, the development of intelligent frequency planning methods and the evaluation of backhaul capacity on overall performance in case of small cells deployment.
Radio access network model with adaptive structure synthesis
Keywords: 5G; мережа радіодоступу; малі комірки; 5G; RAN; small cells